KPIs workshop - Singh, Baljinder (Universiti Teknologi MARA, Sarawak, 2007)
This workshop was an eye opener for most of the participants who were not very familiar with the abbreviation 'KPI'. There were lots of speculations as to what KPI stands for, with some thinking it refers to Key Personnel Intervention. Therefore the workshop was timely and as quipped by one of the participants, "it's a revelation". Thanks to the team of knowledgeable facilitators comprising Prof. Madya Dr. Hjh. Fatimah Bujang, P.M. Iris Syawe Seh Ling and Dr. Kuldip Singh, who covered the following topics: Introduction to KPI, Developing KPI and Implementation of KPI, the participants came to know that Key Performance Indicators, also known as KPIs, are to help an organization define and measure progress toward its goals.